2009
DOI: 10.1111/j.1365-2745.2009.01538.x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental comparison of chemical traits and litter decomposition rates in a diverse range of subarctic bryophyte, lichen and vascular plant species

Abstract: Summary1. Climate change in the subarctic is expected to influence vegetation composition, specifically bryophyte and lichen communities, thereby modifying litter decomposition rates and carbon (C) dynamics of these systems with possible feedbacks to climate. 2. In a 2-year experiment, we investigated decomposition rates and chemical traits of 27 bryophytes, 17 lichens and 5 vascular plants in litter beds in subarctic Sweden. The majority of the sampled cryptogam species are widespread at higher northern latit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
187
4
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(211 citation statements)
references
References 84 publications
(163 reference statements)
17
187
4
3
Order By: Relevance
“…In accordance with our hypothesis, experiment 1 illustrated the importance of cell-wall polysaccharides in explaining the overall low C mineralization rate of Sphagnum litter relative to other moss litters (Lang et al 2009). Whether differences in polysaccharide concentration also explain inter-specific differences in decay rate within Sphagnum, remains to be seen, although recent work (Turetsky et al 2008) indicates that the ratio between easily and poorly degradable polysaccharide fractions is a good predictor for decay rates of Sphagnum species.…”
Section: Discussionsupporting
confidence: 86%
“…In accordance with our hypothesis, experiment 1 illustrated the importance of cell-wall polysaccharides in explaining the overall low C mineralization rate of Sphagnum litter relative to other moss litters (Lang et al 2009). Whether differences in polysaccharide concentration also explain inter-specific differences in decay rate within Sphagnum, remains to be seen, although recent work (Turetsky et al 2008) indicates that the ratio between easily and poorly degradable polysaccharide fractions is a good predictor for decay rates of Sphagnum species.…”
Section: Discussionsupporting
confidence: 86%
“…In this research, the ratio of root and shoot of the receptor were decreased with the increase of leaf litter of E. grandis, and root/shoot in A3 and A2 was significant lower than that of CK (P < 0.05), meanwhile, which in A3 was remarkable lower than A1 (P < 0.05). It showed that the effect of allelopathy on root may more sensitive, and was consistent with the report that allelochemicals firstly acted on membranes of plants' root cells, and influenced the functions of cell membranes through affecting the membrane potential, activity and permeability, ultimately influenced the photosynthesis by a series of biological mechanisms (Lang et al, 2009). …”
Section: Discussionsupporting
confidence: 72%
“…This way of nutrient cycling is similar to the compact, vertical structure of e.g. Sphagnum bogs (Lang et al 2009) and reindeer lichens (Cornelissen et al 2007;Crittenden 1991). Especially the much thicker ectorganic layer in Campylopus is a competitive advantage over the thin layer in most lichen species.…”
Section: N Mineralization and Soil Organic Mattermentioning
confidence: 72%